India since independence - Chandra, Bipan; Mukherjee, Mridula; Mukherjee, Aditya (Gurugram Penguin, 2008)
The story of the forging of India, the world's largest democracy, is a rich andinspiring one. This volume, a sequel to the India's Struggle forIndependence, analyses the challenges India has faced and the successes ithas achieved in the light of its colonial legacy and century-long struggle forfreedom. It covers the framing of the Constitution and the evolution of theNehruvian political and economic agenda and basics of foreign policy; theconsolidation of the nation and contentious issues like party politics in theCentre and the states, the Punjab problem and anti-caste politics anduntouchability. These, along with objective assessments of Jawaharlal Nehru,Indira Gandhi, Jayaprakash Narayan, Lal Bahadur Shastri, Rajiv Gandhi,Vishwanath Pratap Singh, Atal Bihari Vajpayee and Manmohan Singh,constitute a remarkable overview of a nation on the move.
Keywords: History